Growth of (Y1−xCax)Ba2Cu4O8 in ambient pressure and its tri-axial magnetic alignment. (24th August 2015) - Horii, S; Yamaki, M; Shimoyama, J; Kishio, K; Doi, T
Abstract: We report the growth of single crystals in ambient pressure and tri-axial orientation under modulated rotation magnetic fields (MRFs) for (Y1− x Ca x )Ba2 Cu4 O8 [(Y1− x Ca x )124] with x  ≤ 0.1. Rectangular (Y1− x Ca x )124 crystals approximately 50 μ m in size have been successfully grown for x  ≤ 0.1 in a growth temperature region from 650 °C to 750 °C. Their critical temperatures increased with x and exhibited approximately 91 K for x  = 0.1. By applying an MRF of 10 T, pulverised powders of (Y1− x Ca x )124 were tri-axially aligned in epoxy resin at room temperature in a whole x region below x  = 0.1. The magnitude relationship of the magnetic susceptibilities ( χ ) along crystallographic directions for (Y1− x Ca x )124 was χ c  > χ a  > χ b at room temperature and was unchanged with a change in x . From changes in the degrees of the c -axis and the in-plane orientation (Δ ω ) for the (Y1− x Ca x )124 powder samples aligned under three different MRF conditions, it was found that MRFs above at least 1 T were required to achieve almost complete tri-axial alignment with Δ ω  < 5°. Irreversibility lines for H // c were successfully determined even from the powder samples by the introduction of magnetic alignment without using single crystalline samples. The present study indicates that magnetic alignment is a useful process for the fabrication of quasi-single-crystals from the perspective of solid-state physics and the production of cuprate superconducting materials.